A review on Mitragyna speciosa (Rubiaceae) as a prominent medicinal plant based on ethnobotany, phytochemistry and pharmacological activities - Begum, Taslima; Arzmi, Mohd Hafiz; Khatib, Alfi; Helal Uddin, A.B.M.; Abdullah, Maryam Aisyah; Rullah, Kamal; Mat So'ad, Siti Zaiton; Haspi, Nur Fatihah Zulaikha; Sarian, Murni Nazira; Parveen, Humaira; Mukhtar, Sayeed; Ahmed, Qamar Uddin (Taylor & Francis, 2025)
Mitragyna speciosa Korth (kratom) is a tropical indigenous tree of Southeast Asia. It is commonly consumed by the people due to its various pharmacological properties. The leaves of this plant are traditionally used for the treatment of several diseases including pain, fever, cough, anxiety, depression, obesity, diarrhoea, wound healing, diabetes, hypertension as well as for the prevention of cancer and improvement of sexual performance. Phytochemical investigations have confirmed the presence of more than forty alkaloids along with the presence of other bioactive secondary metabolites. Among the alkaloids isolated, mitragynine and 7-hydroxymitragynine along with their derivatives have been widely evaluated and reported to possess various pharmacological effects. Hence, the aim of this review is to shed light on the traditional uses of kratom and the scientific studies to justify the folkloric claims and active principles responsible for the various medicinal effects associated with the leaves of this plant. This review highlights the potential benefits and toxicities associated with M. speciosa leaves along with the phytochemistry. Moreover, the existing gaps in the field of M. speciosa study have been identified along with the future directions to further avail the benefits of this plant species.